The Translation Procedures in Translating the Cultural Words in the Young Adult Novel - Shermy Ismawati (Universitas Pendidikan Indonesia (UPI), 2013)
This research paper is entitled The Analysis of Cultural Words and Context In The Young Adult Novel Translation Entitled “Eragon”. The aim of this research is to find out the procedures which are used in translating the cultural words in the novel and which procedure is mostly applied in the translation of novel Eragon. The writer applied descriptive qualitative method in conducting this research. The primary data were divided into the original and translated versions which were analyzed by using the theory of Newmark (1988). Based on the findings, the writer found that the translator used seven procedures: naturalization, componential analysis, addition, transference, cultural equivalent, couplets, and transposition. Those procedures were used in order to make the translation acceptable and understandable, without changing the essence meaning of the story. By conducting the research, the writer can conclude that translation procedure helps the readers in understanding the message of the story and the different culture of the novel. Keywords : Translation, Translation Procedure, Cultural Words, Young Adult Novel